Chop, fry, watch, learn : Fu Pei-Mei and the making of modern Chinese food - King, Michelle Tien (W.W. Norton & Company, 2024)
In 1949, a young Chinese housewife arrived in Taiwan and transformed herself from a novice to a natural in the kitchen. She launched a career as a cookbook author and television cooking instructor that would last four decades. Years later, in America, flipping through her mother's copies of Fu Pei-mei's Chinese cookbooks, historian Michelle T. King discovered more than the recipes to meals of her childhood. She found, in Fu's story and in her food, a vivid portal to another time, when a generation of middle-class, female home cooks navigated the tremendous postwar transformations taking place across the world.